Sensitivity of Puccinia triticina f. sp. tritici from China to Triadimefon and Resistance Risk Assessment - Ji, Fan (Plant disease, 2023)
Wheat leaf rust, caused by Puccinia triticina f. sp. tritici (Pt), is distributed widely in wheat-producing areas and results in serious yield losses worldwide. In China, leaf rust has been largely controlled with a demethylation inhibitor (DMI) fungicide, triadimefon. Although high levels of fungicide resistance in pathogens have been reported, no field failure of wheat leaf rust to DMI fungicides has been reported in China. A resistance risk assessment of triadimefon to Pt was investigated in the present study. The sensitivity of 197 Pt isolates across the country to triadimefon was determined, and the density distribution of EC50 values (concentration at which mycelial growth is inhibited by 50%) showed a continuous multimodal curve because of the extensive use of this fungicide in wheat production, with a mean value of 0.46 μg/ml. The majority of the tested Pt isolates were sensitive to triadimefon, whereas 10.2% developed varying degrees of resistance. Characterization of parasitic fitness revealed that the triadimefon-resistant isolates exhibited strong adaptive traits in urediniospore germination rate, latent period, sporulation intensity, and lesion expansion rate. No correlation was observed between triadimefon and tebuconazole and hexaconazole, which have the similar mode of action, or pyraclostrobin and flubeneteram, which have different modes of action. Overexpression of the target gene Cyp51 led to the triadimefon resistance of Pt. The risk of resistance to triadimefon in Pt may be low to moderate. This study provided important data for fungicide resistance risk management against wheat leaf rust